Knowledge and behaviors regarding salt intake in Mozambique - Jessen, N (2018)
Background/objectives: Health education and regulatory measures may contribute to lower population salt intake. Therefore, we aimed to describe knowledge and behaviors related to salt intake in Mozambique. Subjects/methods: A cross-sectional evaluation of a representative sample of the population aged 15–64 years (n = 3116) was conducted in 2014/2015, following the Stepwise Approach to Chronic Disease Risk Factor Surveillance, including a 12-question module for evaluation of dietary salt. Results: Three dimensions were identified in the questionnaire, named “self-reported salt intake”, “knowledge of health effects of salt intake”, and “behaviors for control of salt intake”. A total of 7.4% of the participants perceived that they consumed too much/far too much salt and 25.9% reported adding salt/salty seasoning often/always to prepared foods. The proportion considering that it was not important to decrease the salt contents of their diet was 8%, and 16.9% were not aware that high salt intake could be deleterious for health. Prevalences of lack of behaviors for reducing salt intake ranged from 74.9% for not limiting consumption of processed foods, to 95% for not buying low salt alternatives. There were few differences according to socio-demographic variables, but awareness of hypertension was, in general, associated with better knowledge and less frequent behaviors likely to contribute to a high salt intake. Conclusions: Most Mozambicans were aware that high salt intake can cause health problems, but the self-reported salt intake and behaviors for its control show an ample margin for improvement. This study provides evidence to guide population level salt-reducing policies.